Intra-limb kinematic strategies of maximum velocity phase sprint running performances - Gittoes, M.; Bezodis, I.; Wilson, C. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
This study aimed to develop insight into the intra-limb kinematic strategies underpinning athlete- and step-based sprint running performances. Joint centre coordinate data were automatically tracked for maximum velocity phase sprint running trials of six well-trained athletes. The fastest athlete initiated the stance phase with a 16.0º and 3.4º more extended ankle and knee, and a corresponding 5.8º more flexed hip joint compared to the slowest athlete (p<0.05). In contrast, the fastest and slowest steps were typically executed using similar intra-limb kinematics in the stance and recovery phase. More successful athletes may be distinguished by the intra-limb kinematic strategy employed while the robustness of the step-based measures suggested the use of a common, localised strategy regardless of diverse performances.